DEFINITION pr2_confluence__pr2_delta_delta()
TYPE =
       c:C
         .d:C
           .d0:C
             .t0:T
               .t1:T
                 .t2:T
                   .t3:T
                     .t4:T
                       .u:T
                         .u0:T
                           .i:nat
                             .i0:nat
                               .getl i c (CHead d (Bind Abbr) u)
                                 (pr0 t0 t3
                                      (subst0 i u t3 t1
                                           (getl i0 c (CHead d0 (Bind Abbr) u0)
                                                (pr0 t0 t4)(subst0 i0 u0 t4 t2)(ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t))))
BODY =
        assume cC
        assume dC
        assume d0C
        assume t0T
        assume t1T
        assume t2T
        assume t3T
        assume t4T
        assume uT
        assume u0T
        assume inat
        assume i0nat
        suppose Hgetl i c (CHead d (Bind Abbr) u)
        suppose H0pr0 t0 t3
        suppose H1subst0 i u t3 t1
        suppose H2getl i0 c (CHead d0 (Bind Abbr) u0)
        suppose H3pr0 t0 t4
        suppose H4subst0 i0 u0 t4 t2
          by (pr0_confluence . . H3 . H0)
          we proved ex2 T λt:T.pr0 t4 t λt:T.pr0 t3 t
          we proceed by induction on the previous result to prove ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
             case ex_intro2 : x:T H5:pr0 t4 x H6:pr0 t3 x 
                the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                   by (pr0_refl .)
                   we proved pr0 u u
                   by (pr0_subst0 . . H6 . . . H1 . previous)
                   we proved or (pr0 t1 x) (ex2 T λw2:T.pr0 t1 w2 λw2:T.subst0 i u x w2)
                   we proceed by induction on the previous result to prove ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                      case or_introl : H7:pr0 t1 x 
                         the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                            by (pr0_refl .)
                            we proved pr0 u0 u0
                            by (pr0_subst0 . . H5 . . . H4 . previous)
                            we proved or (pr0 t2 x) (ex2 T λw2:T.pr0 t2 w2 λw2:T.subst0 i0 u0 x w2)
                            we proceed by induction on the previous result to prove ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                               case or_introl : H8:pr0 t2 x 
                                  the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                     (h1
                                        by (pr2_free . . . H7)
pr2 c t1 x
                                     end of h1
                                     (h2
                                        by (pr2_free . . . H8)
pr2 c t2 x
                                     end of h2
                                     by (ex_intro2 . . . . h1 h2)
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                               case or_intror : H8:ex2 T λw2:T.pr0 t2 w2 λw2:T.subst0 i0 u0 x w2 
                                  the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                     we proceed by induction on H8 to prove ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                        case ex_intro2 : x0:T H9:pr0 t2 x0 H10:subst0 i0 u0 x x0 
                                           the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                              (h1
                                                 by (pr2_delta . . . . H2 . . H7 . H10)
pr2 c t1 x0
                                              end of h1
                                              (h2
                                                 by (pr2_free . . . H9)
pr2 c t2 x0
                                              end of h2
                                              by (ex_intro2 . . . . h1 h2)
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                      case or_intror : H7:ex2 T λw2:T.pr0 t1 w2 λw2:T.subst0 i u x w2 
                         the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                            we proceed by induction on H7 to prove ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                               case ex_intro2 : x0:T H8:pr0 t1 x0 H9:subst0 i u x x0 
                                  the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                     by (pr0_refl .)
                                     we proved pr0 u0 u0
                                     by (pr0_subst0 . . H5 . . . H4 . previous)
                                     we proved or (pr0 t2 x) (ex2 T λw2:T.pr0 t2 w2 λw2:T.subst0 i0 u0 x w2)
                                     we proceed by induction on the previous result to prove ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                        case or_introl : H10:pr0 t2 x 
                                           the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                              (h1
                                                 by (pr2_free . . . H8)
pr2 c t1 x0
                                              end of h1
                                              (h2
                                                 by (pr2_delta . . . . H . . H10 . H9)
pr2 c t2 x0
                                              end of h2
                                              by (ex_intro2 . . . . h1 h2)
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                        case or_intror : H10:ex2 T λw2:T.pr0 t2 w2 λw2:T.subst0 i0 u0 x w2 
                                           the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                              we proceed by induction on H10 to prove ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                 case ex_intro2 : x1:T H11:pr0 t2 x1 H12:subst0 i0 u0 x x1 
                                                    the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                       (h1
                                                          suppose H13not (eq nat i i0)
                                                             by (sym_not_eq . . . H13)
                                                             we proved not (eq nat i0 i)
                                                             by (subst0_confluence_neq . . . . H12 . . . H9 previous)
                                                             we proved ex2 T λt:T.subst0 i u x1 t λt:T.subst0 i0 u0 x0 t
                                                             we proceed by induction on the previous result to prove ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                case ex_intro2 : x2:T H14:subst0 i u x1 x2 H15:subst0 i0 u0 x0 x2 
                                                                   the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                      (h1
                                                                         by (pr2_delta . . . . H2 . . H8 . H15)
pr2 c t1 x2
                                                                      end of h1
                                                                      (h2
                                                                         by (pr2_delta . . . . H . . H11 . H14)
pr2 c t2 x2
                                                                      end of h2
                                                                      by (ex_intro2 . . . . h1 h2)
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                             we proved ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
(not (eq nat i i0))(ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t)
                                                       end of h1
                                                       (h2
                                                          suppose H13eq nat i i0
                                                             (H14
                                                                by (eq_ind_r . . . H12 . H13)
subst0 i u0 x x1
                                                             end of H14
                                                             (H15
                                                                by (eq_ind_r . . . H2 . H13)
getl i c (CHead d0 (Bind Abbr) u0)
                                                             end of H15
                                                             (H16
                                                                by (getl_mono . . . H . H15)
                                                                we proved eq C (CHead d (Bind Abbr) u) (CHead d0 (Bind Abbr) u0)
                                                                we proceed by induction on the previous result to prove getl i c (CHead d0 (Bind Abbr) u0)
                                                                   case refl_equal : 
                                                                      the thesis becomes the hypothesis H
getl i c (CHead d0 (Bind Abbr) u0)
                                                             end of H16
                                                             (H17
                                                                by (getl_mono . . . H . H15)
                                                                we proved eq C (CHead d (Bind Abbr) u) (CHead d0 (Bind Abbr) u0)
                                                                by (f_equal . . . . . previous)
                                                                we proved 
                                                                   eq
                                                                     C
                                                                     <λ:C.C> CASE CHead d (Bind Abbr) u OF CSort d | CHead c0  c0
                                                                     <λ:C.C> CASE CHead d0 (Bind Abbr) u0 OF CSort d | CHead c0  c0

                                                                   eq
                                                                     C
                                                                     λe:C.<λ:C.C> CASE e OF CSort d | CHead c0  c0 (CHead d (Bind Abbr) u)
                                                                     λe:C.<λ:C.C> CASE e OF CSort d | CHead c0  c0 (CHead d0 (Bind Abbr) u0)
                                                             end of H17
                                                             (h1
                                                                (H18
                                                                   by (getl_mono . . . H . H15)
                                                                   we proved eq C (CHead d (Bind Abbr) u) (CHead d0 (Bind Abbr) u0)
                                                                   by (f_equal . . . . . previous)
                                                                   we proved 
                                                                      eq
                                                                        T
                                                                        <λ:C.T> CASE CHead d (Bind Abbr) u OF CSort u | CHead   tt
                                                                        <λ:C.T> CASE CHead d0 (Bind Abbr) u0 OF CSort u | CHead   tt

                                                                      eq
                                                                        T
                                                                        λe:C.<λ:C.T> CASE e OF CSort u | CHead   tt (CHead d (Bind Abbr) u)
                                                                        λe:C.<λ:C.T> CASE e OF CSort u | CHead   tt (CHead d0 (Bind Abbr) u0)
                                                                end of H18
                                                                suppose H19eq C d d0
                                                                   (H20
                                                                      consider H18
                                                                      we proved 
                                                                         eq
                                                                           T
                                                                           <λ:C.T> CASE CHead d (Bind Abbr) u OF CSort u | CHead   tt
                                                                           <λ:C.T> CASE CHead d0 (Bind Abbr) u0 OF CSort u | CHead   tt
                                                                      that is equivalent to eq T u u0
                                                                      by (eq_ind_r . . . H14 . previous)
subst0 i u x x1
                                                                   end of H20
                                                                   (H21
                                                                      consider H18
                                                                      we proved 
                                                                         eq
                                                                           T
                                                                           <λ:C.T> CASE CHead d (Bind Abbr) u OF CSort u | CHead   tt
                                                                           <λ:C.T> CASE CHead d0 (Bind Abbr) u0 OF CSort u | CHead   tt
                                                                      that is equivalent to eq T u u0
                                                                      by (eq_ind_r . . . H16 . previous)
getl i c (CHead d0 (Bind Abbr) u)
                                                                   end of H21
                                                                   (H22
                                                                      by (eq_ind_r . . . H21 . H19)
getl i c (CHead d (Bind Abbr) u)
                                                                   end of H22
                                                                   by (subst0_confluence_eq . . . . H20 . H9)
                                                                   we proved or4 (eq T x1 x0) (ex2 T λt:T.subst0 i u x1 t λt:T.subst0 i u x0 t) (subst0 i u x1 x0) (subst0 i u x0 x1)
                                                                   we proceed by induction on the previous result to prove ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                      case or4_intro0 : H23:eq T x1 x0 
                                                                         the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                            (H24
                                                                               we proceed by induction on H23 to prove pr0 t2 x0
                                                                                  case refl_equal : 
                                                                                     the thesis becomes the hypothesis H11
pr0 t2 x0
                                                                            end of H24
                                                                            (h1
                                                                               by (pr2_free . . . H8)
pr2 c t1 x0
                                                                            end of h1
                                                                            (h2
                                                                               by (pr2_free . . . H24)
pr2 c t2 x0
                                                                            end of h2
                                                                            by (ex_intro2 . . . . h1 h2)
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                      case or4_intro1 : H23:ex2 T λt:T.subst0 i u x1 t λt:T.subst0 i u x0 t 
                                                                         the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                            we proceed by induction on H23 to prove ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                               case ex_intro2 : x2:T H24:subst0 i u x1 x2 H25:subst0 i u x0 x2 
                                                                                  the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                                     (h1
                                                                                        by (pr2_delta . . . . H22 . . H8 . H25)
pr2 c t1 x2
                                                                                     end of h1
                                                                                     (h2
                                                                                        by (pr2_delta . . . . H22 . . H11 . H24)
pr2 c t2 x2
                                                                                     end of h2
                                                                                     by (ex_intro2 . . . . h1 h2)
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                      case or4_intro2 : H23:subst0 i u x1 x0 
                                                                         the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                            (h1
                                                                               by (pr2_free . . . H8)
pr2 c t1 x0
                                                                            end of h1
                                                                            (h2
                                                                               by (pr2_delta . . . . H22 . . H11 . H23)
pr2 c t2 x0
                                                                            end of h2
                                                                            by (ex_intro2 . . . . h1 h2)
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                      case or4_intro3 : H23:subst0 i u x0 x1 
                                                                         the thesis becomes ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                            (h1
                                                                               by (pr2_delta . . . . H22 . . H8 . H23)
pr2 c t1 x1
                                                                            end of h1
                                                                            (h2
                                                                               by (pr2_free . . . H11)
pr2 c t2 x1
                                                                            end of h2
                                                                            by (ex_intro2 . . . . h1 h2)
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
                                                                   we proved ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
(eq C d d0)(ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t)
                                                             end of h1
                                                             (h2
                                                                consider H17
                                                                we proved 
                                                                   eq
                                                                     C
                                                                     <λ:C.C> CASE CHead d (Bind Abbr) u OF CSort d | CHead c0  c0
                                                                     <λ:C.C> CASE CHead d0 (Bind Abbr) u0 OF CSort d | CHead c0  c0
eq C d d0
                                                             end of h2
                                                             by (h1 h2)
                                                             we proved ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
(eq nat i i0)(ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t)
                                                       end of h2
                                                       by (neq_eq_e . . . h1 h2)
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
          we proved ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t
       we proved 
          c:C
            .d:C
              .d0:C
                .t0:T
                  .t1:T
                    .t2:T
                      .t3:T
                        .t4:T
                          .u:T
                            .u0:T
                              .i:nat
                                .i0:nat
                                  .getl i c (CHead d (Bind Abbr) u)
                                    (pr0 t0 t3
                                         (subst0 i u t3 t1
                                              (getl i0 c (CHead d0 (Bind Abbr) u0)
                                                   (pr0 t0 t4)(subst0 i0 u0 t4 t2)(ex2 T λt:T.pr2 c t1 t λt:T.pr2 c t2 t))))